ANALISIS KUALITAS LAYANAN TERHADAP KEPUASAN TAMU DI BINTAN INTI EXECUTIVE VILLAGE, TELUK LOBAM – BINTAN - Kurniawan, Welli Braham (Jurusan Pariwisata Politeknik Negeri Kupang, 2021)
Every hotel needs to provide the best service so that every guest who stays is satisfied, and this will be the hotel's marketing tool because the guest will share his experience with others. Bintan Inti Executive Villa is a hotel with a residential business hotel concept where guests staying for business purposes. Bintan Inti Executive Villa is only intended for companies in the Lobam Industrial Estate, and usually guests will stay for a long period. In this study, questionnaires were distributed to guests who were staying overnight to measure the level of guest satisfaction with the quality of services provided by the Bintan Inti Executive Villa. Based on the results of the distributed questionnaires, it was obtained that most of the guests who stayed were satisfied with the quality of services provided by Bintan Inti Executive Villa with an average satisfaction rating (mean) of 3.6473 on a scale of 1 to 4.